PENCATATAN PERKAWINAN DI INDONESIA PERSPEKTIF USHUL FIKIH - Nenan Julir (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2017)
Abstract: One of the interesting provisions to be reviewed in Act No. 1 of 1974 is article 2 paragraph (2): “Every marriage is recorded according to the prevailing laws and regulations”. This Law was promulgated on January 2, 1974 and is effective since the issuance of Government Regulation no. In fact, the provisions stipulated in Article 2 paragraph (2) still remain polemic, because there are still many people who have held marriage, but still do not register their marriage to the Officer of Marriage Certificate (VAT) Religious Affairs office. Among Muslims, there is still a firm hold on the understanding that marriage is legal if done according to Islamic law, there is no record and no letter or deed of marriage, because since the time of the Prophet, friend, until the 18th century AD no marriage records were recorded. Therefore, it is necessary to review the recording of this marriage in the perspective of ushul fiqh. From the results of this study. it can be concluded that marriage registration as regulated in Act No. 1 of 1974 when viewed through ushul fiqh fiqh, it was based on mashlahah mursalah.